The Executorial Power of the Stipulation on The Division of Joint Property Based on a Peace Agreement In a Divorce Case - Yustitia Ismail, Ravilka; Hartini, Hartini (Universitas Negeri Semarang, 2025)
The purpose of this study is to determine and analyze the executorial power of the verdict regarding the division of joint property on the basis of a peace agreement as outlined in a divorce verdict in the Religious Court, the differences in views between the Judges of the Banjar City Religious Court in West Java and the Head of the Banjar City Land Office in West Java regarding the executorial power in the peace agreement as outlined in divorce verdict number 722/Pdt.G/2020/PA/Bjr, and solutions to the differences in views regarding the executorial power in divorce verdict number 722/Pdt.G/2020/PA/Bjr. This type of research is empirical normative research. Data obtained based on library data research, namely primary, secondary and tertiary legal materials, then continued with primary data. The collected data is analyzed qualitatively and presented descriptively. The results showed that the executorial power in divorce verdict number 722/Pdt.G/2020/PA.Bjr is in the irah-irah which reads “For the Sake of Justice Based on God Almighty”. The decision is condemnatory or punishment imposed on the applicant and respondent to implement the peace agreement. The transfer of land rights based on a court decision can be carried out based on the provisions of Article 55 of Government Regulation Number 24 of 1997 or using a grant deed provided that the clause contains a peace agreement resulting from the mediation on November 30, 2020.